PEMBERIAN PELATIHAN WEBINAR STRATEGI PENGELOLAAN (COPING) STRES MENGHADAPI PANDEMI COVID-19 - Fitriani, Arbania; Kembangkasih, Andin (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Coping strategies are activities carried out by individuals, whether consciously or not, which aim to reduce or eliminate a threat, both internal and external. At the beginning of 2020, the world was shocked by the Covid-19 outbreak which infected almost all countries in the world. Especially in Indonesia itself, the Government has issued a disaster emergency status starting from February 29, 2020 to May 29, 2020 related to this virus pandemic with a total time of 91 days. This situation certainly makes most people feel anxious, panic and fearful. In this training, the author also wants to see what coping strategies the webinar participants are doing. The method used to see the coping strategy uses a quantitative approach with the adapted stress coping strategy scale measuring instrument. The research sample consisted of 86 lecturers from various faculties at Esa Unggul University. Referring to the results of statistical tests, it was found that respondents used more planning stress coping strategies, namely 3.78, followed by the religiosity aspect of 3.71 and the three aspects of seeking social support of 3.70.Ã‚Â Keywords: coping strategies, stress, COVID-19